2006
DOI: 10.1093/europace/euj038
|View full text |Cite
|
Sign up to set email alerts
|

The role of pacing mode in the development of atrial fibrillation

Abstract: Asynchronous ventricular pacing has been shown to increase the risk of development of atrial fibrillation (AF) because of various mechanisms: retrograde atrioventricular (AV) conduction with increase in atrial pressure causing acute atrial stretch and reverse flow in the pulmonary veins, mitral regurgitation, reduced coronary blood flow, adverse neuroendocrine reactions, etc. Dual-chamber pacing preserves atrioventricular synchrony. However, in randomized multicentre trials comparing VVI(R) with DDD(R) pacing,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 56 publications
(60 reference statements)
0
9
0
Order By: Relevance
“…This is frequent when AF is accompanied by AV block, as well as ventricular and AV junctional tachycardia [25,52]. Moreover, the incidence of AF is about 50% in patients with a paced ventricular rhythm over 2 years [57]. A negative outcome is also obtained when these algorithms deal with OR rhythms showcasing irregular RR interval series, such as sinus arrhythmia [52].…”
Section: Discussionmentioning
confidence: 99%
“…This is frequent when AF is accompanied by AV block, as well as ventricular and AV junctional tachycardia [25,52]. Moreover, the incidence of AF is about 50% in patients with a paced ventricular rhythm over 2 years [57]. A negative outcome is also obtained when these algorithms deal with OR rhythms showcasing irregular RR interval series, such as sinus arrhythmia [52].…”
Section: Discussionmentioning
confidence: 99%
“…Recent observational and controlled studies in patients with SND have also suggested that ventricular dyssynchrony imposed by right ventricular apical pacing increases the risk of atrial fibrillation (AF), despite the preservation of AV synchrony. [4][5][6][7][8][9] Related observations were made in the PIPAF (Pacing In Prevention of Atrial Fibrillation) study where, after controlling for the percentage of ventricular pacing (Vp), AF prevention algorithms appeared to alleviate the AF burden only when spontaneous conduction was preserved. 10 The usual practice, nevertheless, consists of (1) implanting a dual chamber pacing system to eliminate the risk of ventricular standstill due to AV block and (2) programming a long AV delay, although the latter is mostly ineffective and associated with a high rate of pacemaker-mediated tachycardia.…”
Section: Introductionmentioning
confidence: 96%
“…The main advantages of AAI pacing are (1) the preservation of hemodynamic function by enabling spontaneous ventricular activation and (2) sparing of the pulse generator battery. Recent observational and controlled studies in patients with SND have also suggested that ventricular dyssynchrony imposed by right ventricular apical pacing increases the risk of atrial fibrillation (AF), despite the preservation of AV synchrony 4–9 . Related observations were made in the PIPAF (Pacing In Prevention of Atrial Fibrillation) study where, after controlling for the percentage of ventricular pacing (Vp), AF prevention algorithms appeared to alleviate the AF burden only when spontaneous conduction was preserved 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, only patients with preserved LV function and who did not present with AF within 3 months after pacemaker implantation were included; moreover, patients with ventriculoatrial conduction were excluded, as this condition is known to increase the risk of RV pacing-induced AF. 19 In previous studies of sinus node disease, high cumul%VP was found to be associated with an increased incidence of AF, 1,2,20 but the relationship between cumul%VP and the incidence of RV pacing-induced AF had not been confirmed in patients presenting with AV block. To the best of our knowledge, the present study is the longest follow-up analysis in patients who received RV septal pacing for AV block.…”
Section: Correlation Between Cumul%vp and Post-implantation Af In Patmentioning
confidence: 90%